واقع إدارة الأزمات التعليمية في جامعة تشرين من وجهة نظر أعضاء الهيئة التعليمية والإدارية فيها - علي نايفة (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The study aims at defining the reality of educational-management crisis which faces Tishreen University from the view point of the staff and administrative members and at defining the differences in the administrative methods of crisis-management according to these variables (the scientific qualification, the experience, the faculty, and the sort of job). In addition to some suggestions concerning the best Administrative methods of Crisis-management at Tishreen University, and to achieve the objectives of this research, a questionnaire has been applied on a sample of (278) individuals during the academic year of (2014 - 2015). It consisted of (52) statements distributed into five sections (planning of educational management, the process of communication during the crisis, the importance of information in crisis-management, the financial and human abilities which are variable to Crisis management, and the extent of works credibility and their belonging to the University). The validity of the questionnaire was approved depending on some specializers and experts in both the education and economics faculties at Tishreen University. There were (9) referees, the total reliability factor was (0.755). The result of the research proved that the crisis-management at the University was of an average level in addition to statistical significant difference concerning the degree of crisis-management according to the variable of the scientific qualification. It also showed no statistical significant difference according to the variables of experience, the faculty, and the sort of job. The researcher suggested preparing training sessions and specialized workshops in crisis-management at the University to raise some awareness about it. هدف البحث إلى تحديد واقع إدارة الأزمات التي تواجه جامعة تشرين من وجهة نظر أعضاء الهيئة التعليمية والإدارية فيها، وتعرف الفروق في الأساليب الإدارية المتبعة في إدارة الأزمات تبعاً للمتغيرات التالية (المؤهل العلمي، الخبرة، نوع الكلية، المسمى الوظيفي)، والتوصل إلى مقترحات حول الأساليب الإدارية الأفضل لإدارة الأزمات في الجامعة، ولتحقيق أهداف البحث طبقت استبانة على عينة شملت (278) فرداً خلال الفصل الدراسي الأول من العام الدراسي 2014 – 2015، وقد تألفت الاستبانة من (52) عبارة، موزعة إلى خمسة مجالات، هي: (التخطيط لإدارة الأزمات، عملية الاتصال في الأزمات، أهمية المعلومات في إدارة الأزمات، الإمكانيات المادية والبشرية المتوافرة لإدارة الأزمات، مدى ولاء العاملين وانتماءهم للجامعة)، وتم التحقق من صدق الاستبانة بعرضها على مجموعة من الخبراء والمختصين في كليتي التربية والاقتصاد بجامعة تشرين، وبلغ عددهم (9) محكمين، وقد بلغ معامل الثبات الكلي للاستبانة (0.755). وتوصلت نتائج البحث إلى أن إدارة الأزمات التعليمية في الجامعة جاءت بدرجة متوسطة. كما توصلت إلى وجود فروق دالة إحصائياً حول درجة إدارة الأزمات التعليمية تبعاً لمتغير المؤهل العلمي، لصالح حملة الدكتوراه، وعدم وجود فروق دالة إحصائياً تبعاً للمتغيرات الآتية (الخبرة، نوع الكلية، المسمى الوظيفي). وقدم البحث مقترحات عديدة أهمها: إقامة دورات تدريبية وورشات عمل متخصصة في إدارة الأزمات للعاملين بالجامعة لزيادة وعيهم بمجال إدارة الأزمات.